Effect of Immobilisation on Neuromuscular Function In Vivo in Humans: A Systematic Review - Campbell, Matthew (Sports Med, 2019)
BACKGROUND: Muscle strength loss following immobilisation has been predominantly attributed to rapid muscle atrophy. However, this cannot fully explain the magnitude of muscle strength loss, so changes in neuromuscular function (NMF) may be involved. OBJECTIVES: We systematically reviewed literature that quantified changes in muscle strength, size and NMF following periods of limb immobilisation in vivo in humans. METHODS: Studies were identified following systematic searches, assessed for inclusion, data extracted and quality appraised by two reviewers. Data were tabulated and reported narratively. RESULTS: Forty eligible studies were included, 22 immobilised lower and 18 immobilised upper limbs. Limb immobilisation ranged from 12 h to 56 days. Isometric muscle strength and muscle size declined following immobilisation; however, change magnitude was greater for strength than size. Evoked resting twitch force decreased for lower but increased for upper limbs. Rate of force development either remained unchanged or slowed for lower and typically slowed for upper limbs. Twitch relaxation rate slowed for both lower and upper limbs. Central motor drive typically decreased for both locations, while electromyography amplitude during maximum voluntary contractions decreased for the lower and presented mixed findings for the upper limbs. Trends imply faster rates of NMF loss relative to size earlier in immobilisation periods for all outcomes. CONCLUSIONS: Limb immobilisation results in non-uniform loss of isometric muscle strength, size and NMF over time. Different outcomes between upper and lower limbs could be attributed to higher degrees of central neural control of upper limb musculature. Future research should focus on muscle function losses and mechanisms following acute immobilisation. REGISTRATION: PROSPERO reference: CRD42016033692. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40279-019-01088-8) contains supplementary material, which is available to authorized users.